The Correlation of Students’ Speaking Anxiety and Speaking Performance in Second Grade at SMA Negeri 1 Sipahutar - Tampubolon, Helendina; Sinaga, Nenni Triana; Lestari, Febrika Dwi (ALACRITY : Journal of Education, 2024)
Improving students' speaking skills is important in the language learning process. This study aims to determine the correlation between speaking anxiety and speaking performance in students and determine what speaking anxiety factors affect students' speaking performance in the second grade of SMA Negeri 1 Sipahutar. The research method used is quantitative. data was collected through speaking tests, questionnaires, and interviews. The result of the data analysis shows the result on correlation coefficient (r = 0.394) which is defined as a positive relationship between anxiety and speaking performance, defined that there is a positive relationship between speaking anxiety and speaking performance and the factors that influence speaking anxiety and students' speaking performance is the Trait Anxiety factor. The hypothesis test states that there is a significant relationship between speaking anxiety and students' speaking performance and the hypothesis test states that there is a significant relationship between speaking anxiety and student performance.